Performance Evaluation of Wira-wiri FD09 Feeder Analysis of Load Factor, Headway, and Travel Time - Wahju Herijanto; Prathita Muti'a Yuzaeva (Universitas Islam Raden Rahmat, Malang, 2026)
Transportation serves as the primary enabler of mobility for Surabaya City's residents. To enhance public transport service quality, the Surabaya City Government operates the Feeder Wirawiri Suroboyo, including the FD09 route from Menanggal Terminal to Manukan Terminal. This study evaluates the operational performance of the FD09 feeder using key parameters load factor, headway, and travel time derived from route and vehicle surveys. Findings reveal that most vehicles operate below the ideal 70% load factor, with an average headway of 26 minutes, failing to meet Directorate General of Land Transportation standards. One-way travel time from Menanggal to Manukan Terminal averages 173 minutes for a round trip, and 160 minutes in the reverse direction; however, the extended headway results in excessive passenger wait times, violating service norms. The results indicate that Feeder Wirawiri Suroboyo requires service improvements, such as that routes can be rerouted with bus stop points that have high passenger demand and adding vehicles to reduce headway and waiting times, thereby better fulfilling community mobility demands.